(untitled) (Journal of the College of Basic Education, 2022)
The aim of the study is to identify the most important Biomechanical variables for the players in the penalty shoots as well as the preparation of special exercises for goalkeepers in football according to the most important variables and to identify the impact of special exercises prepared in the expectations of goalkeepers for football and to identify the evolution rates of the three variables of research The researcher used the experimental method in the method of equal samples as a way to solve the problem of research using a research sample consisting of 24 goalkeeper and the researcher reached several conclusions, the most important of which is that the exercises of the group have a clear and significant impact in increasing the Prediction of movement the researcher also recommended several recommendations, especially the adoption of special exercises for training goalkeepers for all age groups and be part of the training curriculum in the (general. private. and competitive)preparation because the penalty shoot can be counted on the team at any time of the game if the goalkeeper is trained will be helpful to his team at that moment It and he may be a reason to win that tournament or match